Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru di Sekolah Dasar Negeri - Mariyana, Dian; Wuryandini, Endang; Rasiman, Rasiman (PGRI Kota Semarang, 2024)
Teacher performance can be said to be of high quality if it produces good work and can lead students to achieve achievements. Good coaching and mentoring carried out by the principal makes the enthusiasm and motivation of teachers increase so that teacher performance gets maximum results. The aims of this study are: 1) to describe and analyze the principal's strategic planning in improving teacher performance, 2) to describe and analyze the implementation of the principal's strategy in improving teacher performance, 3) to describe and analyze the evaluation of the principal's strategy in improving teacher performance. at the State Elementary School Wanoja 02 Subdistrict Salem Regency Brebes. The research approach used is qualitative. Qualitative research design through three stages, namely: orientation, exploration focus, and data analysis. Data collection techniques are interviews, observation and documentation. This research uses triangulation technique. Data analysis with three steps: data reduction, presenting data, and drawing conclusions. The results of the study indicate that: 1) The principal provides discipline and exemplary guidance which is included in the principal's strategic planning activities in improving teacher performance. 2) Principals carry out seminars and training activities, collaborate with other educational institutions, bring in experts, conduct regular academic supervision, provide adequate facilities and infrastructure that are included in the activities of implementing the principal's strategy in improving teacher performance. 3) The principal evaluates the planning and implementation aspects of the principal's strategy in improving teacher performance at the State Elementary School of Wanoja 02 Subdistrict Salem Regency Brebes. Conclusion The principal's strategy in improving teacher performance has been carried out through steps or procedures in accordance with management principles which consist of three activities, namely, planning, implementation, and evaluation. The author suggests that school principals are expected to make and arrange planning, implementation and evaluation well.